Method for detecting electrolyte dendrites in solid-state battery

By introducing EU3+to preparing fluorescent electrolytes in the electrolytes of solid -state batteries, and combined with CLSM technology, the existing detection method is difficult to accurately detect the internal branches of the battery, and the effect of non -destructive, deep analysis and life prediction is achieved.

CN119375195APending Publication Date: 2025-01-28BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411516360.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing detection methods are difficult to accurately find sodium/lithium dendrites in solid-state batteries, and electrolytes are often required to destroy, affecting the observation results.

Method used

By introducing EU3+into the electrolytes of solid -state batteries, preparing fluorescent electrolytes, and using laser co -focusing microscopic technology (CLSM) to detect the distribution of sodium/lithium branches in fluorescent electrolytes.

Benefits of technology

The non -broken detection of the distribution of sodium/lithium -lithium crystal internal sodium/lithium branches can be implemented. In -depth analysis can be performed, three -dimensional images are constructed, and the life of electrolyte is predicted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119375195A_ABST
    Figure CN119375195A_ABST
Patent Text Reader

Abstract

The invention relates to a method for detecting electrolyte dendrites in a solid-state battery, and belongs to the technical field of alkali metal solid-state battery detection. According to the method, the prepared fluorescent electrolyte is tested by using a CLSM technology, so that the distribution of dendrites in the fluorescent electrolyte after charge-discharge circulation of the alkali metal solid electrolyte is detected. By utilizing the technology, the dendritic crystal distribution of the electrolyte with the fluorescence characteristic can be detected, for example, elements such as Eu < 3 + >, Tb < 3 + >, Sm < 3 + > and Dy < 3 + > are doped in NASICON, the fluorescent electrolyte can be prepared, and a corresponding solid-state battery can be assembled, so that the dendritic crystal distribution of the charged and discharged fluorescent electrolyte can be detected by utilizing the CLSM technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for detecting electrolyte dendrites in a solid-state battery, belonging to the technical field of alkali metal solid-state battery detection. Background Art

[0002] With the continuous growth of global energy demand and the increasing severity of climate change problems, the development and utilization of renewable energy has become a goal. In this context, energy storage technology, especially efficient, safe and sustainable battery technology, has become particularly important. As an emerging energy storage technology, all-solid-state alkali metal batteries (SMBs) have gradually attracted widespread attention due to their abundant sodium resources, low cost and high safety. SMBs use non-flammable solid electrolytes instead of traditional organic liquid electrolytes, which significantly improves the safety of the battery. Common sodium / lithium solid electrolytes are divided into inorganic electrolytes, organic polymer electrolytes and composite electrolytes. Sodium ion conductor in inorganic electrolyte (NASICON), with the chemical formula Na3Zr2Si2PO 12 , LLZTO lithium electrolyte, chemical formula is Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 , which has attracted widespread attention due to its excellent stability and high ionic conductivity. Despite this, SMBs still face many challenges in practical applications, among which the formation and growth of sodium / lithium dendrites is one of the main issues affecting their performance and safety. Sodium / lithium dendrites not only cause internal short circuits and capacity decay of the battery, but may also cause thermal runaway, posing serious safety hazards.

[0003] Existing monitoring methods have certain limitations, which are mainly manifested in the following aspects. The observation of sodium dendrites by scanning electron microscopy (SEM) and other characterization methods requires a strict test environment and generally requires the destruction of the electrolyte. It is difficult to accurately find the position of the dendrites inside by observing the cross-section of the solid electrolyte, and the mechanical behavior during the destruction of the electrolyte may affect the observation of the sodium / lithium dendrites. The use of solid-state nuclear magnetic resonance technology to detect sodium / lithium dendrites requires more serious destruction of the electrolyte, and only detects the signal of the existence of sodium / lithium dendrites, making it difficult to determine the location of the sodium / lithium dendrites and other information. Summary of the invention

[0004] In view of the above problems, the present invention proposes a method for detecting electrolyte dendrites in solid-state batteries. 3+It is introduced into the electrolyte of the solid-state battery to prepare a fluorescent electrolyte, and its fluorescence characteristics are used in combination with confocal laser microscopy (CLSM) to detect the distribution of sodium / lithium dendrites in the fluorescent electrolyte. The present invention will not be destructive to the solid electrolyte, and can perform a certain degree of in-depth analysis to detect the distribution of sodium / lithium dendrites inside the electrolyte. The surface of the fluorescent electrolyte is scanned layer by layer using CLSM to construct an internal three-dimensional image, analyze the distribution of sodium / lithium dendrites inside the fluorescent electrolyte at a certain depth, and predict the life of the electrolyte by changes in the fluorescence intensity inside the electrolyte.

[0005] The technical solution of the present invention is:

[0006] A method for detecting electrolyte dendrites in a solid-state battery, the method comprising the steps of:

[0007] The first step is to prepare the fluorescent electrolyte;

[0008] In the second step, CLSM technology was used to detect the dendrite distribution inside the fluorescent electrolyte.

[0009] In the first step, the fluorescent electrolyte is a fluorescent NASICON sodium electrolyte, a PVDF-HFP sodium electrolyte, a LLZTO lithium electrolyte, or a PVDF-HFP lithium electrolyte.

[0010] The method for preparing fluorescent NASICON sodium electrolyte is:

[0011] Raw materials include Na2CO3, ZrO(NO3)2, SiO2, NaH2PO4, Eu2O3;

[0012] The molar ratio of Na2CO3, ZrO(NO3)2, SiO2 and NaH2PO4 in the raw materials is 1.5:2:2:1, and Eu2O3 accounts for 2%-20% of the total mass of the raw materials.

[0013] After the raw materials are mixed, they are ground by a ball mill to obtain a mixture, which is then pre-fired at 900-1000°C to obtain pre-fired powder. The pre-fired powder is then granulated and pressed into tablets. The obtained tablets are pyrolyzed in air to remove the PVB binder used in the granulation, and then sintered again at 1150-1250°C to obtain the fluorescent NASICON electrolyte.

[0014] The preparation method of PVDF-HFP sodium electrolyte is:

[0015] The raw materials include: NaTFSI, PVDF-HFP, EuF3, dimethylformamide (DMF);

[0016] The mass ratio of NaTFSI, PVDF-HFP, and EuF3 in the raw materials is 5:7.5:1, and DMF is used as the solvent, so that the concentration of NaTFSI ranges from 16 to 33 mg mL -1 between.

[0017] NaTFSI and PVDF-HFP were weighed and dissolved in DMF, magnetically stirred at 30 ° C for 12 h, and then EuF3 was added and stirred for 12 h. The resulting solution was then coated on a polytetrafluoroethylene (PTFE) plate with a spatula and dried in a vacuum oven at 50 ° C for at least 48 h. Finally, the obtained electrolyte membrane was stored in a glove box filled with argon and recorded as PVDF-HFP-Na.

[0018] The preparation method of LLZTO lithium electrolyte is:

[0019] The raw materials include LiOH·H2O, ZrO2, La2O3, Ta2O5, and Eu2O3;

[0020] The molar ratio of LiOH·H2O, La2O3, ZrO2, Ta2O5 and Eu2O3 in the LLTTO raw material is: 6.4:2.95:1.4:0.6:0.05.

[0021] La2O3 was pre-calcined at 1000℃ for 6h, and the raw material was ball-milled in a ball mill for 4h, using isopropanol as a solvent. Then the isopropanol was dried at 80℃, and the dried mixture was pre-calcined at 950℃ for 10h. The pre-calcined product was again ground in 2-propanol using a ball mill for 4h, and dried at 80℃ to remove the isopropanol. Then it was calcined at 1200℃ for 6h to obtain the LLZTO luminescent electrolyte, which was recorded as LLZTO-0.05Eu.

[0022] The preparation method of PVDF-HFP lithium electrolyte is:

[0023] Raw materials include: LiTFSI, PVDF-HFP, EuF3, DMF;

[0024] The mass ratio of LiTFSI, PVDF-HFP, and EuF3 in the raw materials is 7.5:7.5:1, and DMF is used as the solvent, so that the concentration of LiTFSI is in the range of 25-50 mg mL -1 between.

[0025] LiTFSI and PVDF-HFP were weighed and dissolved in dimethylformamide, magnetically stirred at 30 ° C for 12 h, and then EuF3 was added and stirred for 12 h. The resulting solution was then coated on a polytetrafluoroethylene (PTFE) plate with a spatula and dried in a vacuum oven at 50 ° C for at least 48 h. Finally, the obtained electrolyte membrane was stored in a glove box filled with argon and recorded as PVDF-HFP-Li.

[0026] In the second step, the method of using CLSM technology to detect the internal dendrite distribution of NASICON fluorescent solid electrolyte is:

[0027] First, assemble a solid-state battery. The positive electrode of the solid-state battery is sodium vanadium phosphate positive electrode, the negative electrode is metallic sodium, and the solid-state electrolyte is the fluorescent NASICON electrolyte obtained in the first step. The solid-state battery is assembled in the order of negative electrode shell, shrapnel, stainless steel sheet, sodium sheet, fluorescent electrolyte, and positive electrode sheet. At a set current density, the assembled solid-state battery is charged and discharged. After a set number of cycles, the solid-state battery is disassembled and the electrolyte in the solid-state battery is detected by CLSM.

[0028] When using CLSM for detection, the laser excitation wavelength of CLSM is 405nm, and the depth analysis of the fluorescent NASICON electrolyte is carried out at a speed of 4-10μm / min, and the image is collected layer by layer. The analysis depth is 15-30μm.

[0029] The assembled solid-state battery is charged and discharged at a current density of 100 mA g -1 , the number of charge and discharge cycles is 1100.

[0030] Beneficial Effects

[0031] 1. Eu 3+ Elements are doped into fluorescent electrolytes to prepare fluorescent electrolytes with fluorescent properties; the fluorescent electrolytes are prepared, and their fluorescent properties are combined with laser confocal microscopy to detect the distribution of dendrites inside the electrolyte. Previous technologies, such as SEM, require the destruction of the electrolyte and observation of dendrites through cross-sections. The present invention can be non-destructive, and the excitation light source is laser, which has stronger energy, better concentration and energy intensity, can detect the internal situation of the electrolyte to a certain depth, and construct a three-dimensional graph, so as to intuitively analyze the formation and distribution of sodium / lithium dendrites.

[0032] 2. Use CLSM technology to test the prepared fluorescent electrolyte to detect the distribution of sodium / lithium dendrites inside the fluorescent electrolyte after SMBs charge and discharge cycles. This technology can be used to detect the dendrite distribution of most electrolytes with fluorescent properties, such as Tb doped in NASICON and LLZTO. 3+ ,Sm 3+,Dy 3+ Eu can also be added to polymer electrolytes, such as polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile, polyvinyl pyrrolidone, etc. to prepare fluorescent electrolytes, thereby realizing the observation of sodium dendrites using CLSM technology. 3+ , a fluorescent electrolyte with uniform fluorescence distribution can also be prepared, so that the distribution of sodium / lithium dendrites can be detected using CLSM technology.

[0033] The present invention provides a method for detecting electrolyte dendrites in a solid-state battery, wherein a fluorescent electrolyte is prepared by introducing Eu3+ into the electrolyte of the solid-state battery. As a fluorescent probe, Eu3+ has unique fluorescence characteristics, high sensitivity and high resolution, and can emit red fluorescence signals under a laser excitation light source, which is conducive to accurately detecting the distribution of dendrites in the electrolyte. By optimizing the preparation process of the electrolyte, the uniform distribution and stability of Eu3+ in the electrolyte are ensured to obtain a stable and reliable fluorescence signal.

[0034] The fluorescent electrolyte is scanned layer by layer using CLSM technology. CLSM technology has high resolution and three-dimensional imaging capabilities, and can obtain fluorescent signals of different depths of the fluorescent electrolyte by scanning layer by layer. By processing and analyzing these fluorescent signals, a three-dimensional image of the inside of the electrolyte is constructed, and by analyzing the intensity and distribution of the fluorescent signal, the distribution of sodium / lithium dendrites inside the electrolyte can be accurately detected. This method has the characteristics of non-destructiveness, does not cause any damage to the electrolyte, and ensures the integrity and functionality of the electrolyte. At the same time, through the high resolution of CLSM technology, the microstructure inside the electrolyte can be deeply analyzed, and a detailed dendrite distribution map can be provided, providing a scientific basis for further research and optimization of solid-state batteries. In addition, the method of the present invention can also predict the service life of the electrolyte by monitoring the changes in the fluorescent signal. As the charge and discharge cycle proceeds, the sodium / lithium dendrites continue to grow, and the fluorescence of the fluorescent electrolyte will be destroyed, resulting in the attenuation of the fluorescence intensity. By monitoring the changes in the fluorescent signal of the electrolyte after different cycles, the health status and remaining life of the electrolyte can be evaluated, providing a basis for the maintenance and replacement of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The fluorescence excitation spectrum of the NASICON electrolyte prepared in Example 1 (the corresponding emission wavelength is E m =619nm);

[0036] Figure 2 The fluorescence emission spectrum of the NASICON electrolyte prepared in Example 1 (the corresponding excitation wavelength is E x =395nm);

[0037] Figure 3CLSM layer-by-layer analysis of the NASICON electrolyte prepared in Example 1 after 1100 cycles of charge and discharge (current density is 100 mAg -1 ).

[0038] Figure 4 CLSM 3D reconstruction image of the NASICON electrolyte prepared in Example 1 after 1100 cycles of charge and discharge (current density is 100 mAg -1 ). DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0040] Example 1

[0041] A method for detecting electrolyte dendrites in a solid-state battery, the method comprising the steps of:

[0042] The first step is to prepare fluorescent NASICON electrolyte;

[0043] In the second step, the CLSM technique was used to detect the dendrite distribution inside the NASICON electrolyte;

[0044] In the first step, the method for preparing the fluorescent NASICON electrolyte is:

[0045] Raw materials include Na2CO3, ZrO(NO3)2, Eu2O3, SiO2, NaH2PO4;

[0046] The molar ratio of Na2CO3, ZrO(NO3)2, SiO2 and NaH2PO4 in the raw materials is 1.5:2:2:1, and Eu2O3 accounts for 5% of the total mass.

[0047] After the raw materials are mixed, they are ground by a ball mill to obtain a mixture, and then pre-calcined at 1000°C to obtain a pre-calcined powder, which is then granulated and pressed into a sheet in a mold with a diameter of 10 mm. The obtained sheet is pyrolyzed in air to remove the PVB binder used in the granulation, and then sintered again at 1200°C to obtain a molded fluorescent NZSP electrolyte, which is recorded as NZSP-5%EO. The excitation wavelength of the obtained fluorescent NZSP-%EO electrolyte is 395nm, as shown in FIG. Figure 1 As shown, it is close to the standard excitation wavelength of CLSM (405 nm), which can excite the prepared fluorescent NZSP-5% EO electrolyte, and the main fluorescence emission wavelength of the fluorescent NZSP electrolyte is 619 nm, as shown in FIG. Figure 2As shown, it exhibits bright red fluorescence, which can well avoid the influence of background light; the fluorescence emission spectrum of the NZSP-5% EO electrolyte prepared in Example 1 was tested using the measured optimal excitation wavelength, and fluorescence emission peaks appeared at 593nm, 619nm, 655nm and 704nm, which are respectively attributed to Eu 3+ exist 5 D0→ 7 F1, 5 D0→ 7 F2, 5 D0→ 7 F3, and 5 D0→ 7 Transition at F4.

[0048] In the second step, the method of using CLSM technology to detect the distribution of dendrites inside the NASICON electrolyte is:

[0049] First, a solid-state battery is assembled. The positive electrode of the solid-state battery is sodium vanadium phosphate positive electrode, the negative electrode is metallic sodium, and the solid-state electrolyte is the fluorescent NZSP-5% EO electrolyte obtained in the first step. The solid-state battery is assembled in the order of negative electrode shell, shrapnel, stainless steel sheet, sodium sheet, fluorescent NZSP-5% EO electrolyte, and positive electrode sheet. The assembled solid-state battery is subjected to charge and discharge tests at a set current density. After a set number of cycles, the solid-state battery is disassembled and the electrolyte in the solid-state battery is detected by CLSM.

[0050] When using CLSM for detection, the laser excitation wavelength of CLSM is 405nm, and the depth analysis of the fluorescent NZSP-5% EO electrolyte is carried out at a speed of 5-10μm / min, and the image is collected layer by layer. The analysis depth is 30μm. Figure 3 and Figure 4 As shown, the results show that black spots appear inside the NZSP-5% EO electrolyte after cycling, and the fluorescence is destroyed, indicating that sodium dendrites are generated inside the NZSP-5% EO electrolyte, thereby destroying the fluorescence and causing fluorescence quenching, thus achieving non-destructive and intuitive detection of the formation and distribution of dendrites inside the NZSP-5% EO electrolyte.

[0051] Example 2

[0052] A method for detecting electrolyte dendrites in a solid-state battery, the method comprising the steps of:

[0053] The first step is to prepare the fluorescent PVDF-HFP-Na electrolyte;

[0054] In the second step, the CLSM technique was used to detect the dendrite distribution inside the PVDF-HFP sodium electrolyte;

[0055] In the first step, the method for preparing the fluorescent PVDF-HFP sodium electrolyte is:

[0056] Raw materials include: NaTFSI, PVDF-HFP, EuF3, DMF

[0057] The mass ratio of NaTFSI, PVDF-HFP, and EuF3 in the raw materials is 5:7.5:1, and DMF is used as the solvent, so that the concentration of NaTFSI ranges from 16 to 33 mg mL -1 between.

[0058] Weigh 0.5g NaTFSI and 0.75g PVDF-HFP respectively and dissolve them in 15mL DMF, stir them magnetically at 30℃ for 12h, then add 0.1g EuF3, continue stirring for 12h, then apply the obtained solution on a polytetrafluoroethylene (PTFE) plate with a spatula and dry it in a vacuum oven at 50℃ for at least 48h. Finally, store the obtained electrolyte membrane in a glove box filled with argon. When assembling the battery, cut the electrolyte membrane into 8mm diameter discs for use.

[0059] In the second step, the method of using CLSM technology to detect the dendrite distribution inside the PVDF-HFP-Na electrolyte is:

[0060] First, a solid-state battery is assembled. The positive electrode of the solid-state battery is sodium vanadium phosphate positive electrode, the negative electrode is metallic sodium, and the solid-state electrolyte is the fluorescent PVDF-HFP-Na electrolyte obtained in the first step. The solid-state battery is assembled in the order of negative electrode shell, shrapnel, stainless steel sheet, sodium sheet, fluorescent PVDF-HFP-Na electrolyte, and positive electrode sheet. The assembled solid-state battery is subjected to charge and discharge tests at a set current density. After a set number of cycles, the solid-state battery is disassembled and the electrolyte in the solid-state battery is detected by CLSM.

[0061] Example 3

[0062] A method for detecting electrolyte dendrites in a solid-state battery, the method comprising the steps of:

[0063] The first step is to prepare the fluorescent LLZTO-0.05Eu electrolyte;

[0064] In the second step, the CLSM technique was used to detect the dendrite distribution inside the LLZTO-0.05Eu electrolyte;

[0065] In the first step, the method for preparing the fluorescent LLZTO-0.05Eu electrolyte is:

[0066] The raw materials include LiOH·H2O, ZrO2, La2O3, Ta2O5, and Eu2O3;

[0067] The molar ratio of LiOH·H2O, La2O3, ZrO2, Ta2O5 and Eu2O3 in the LLTTO raw material is: 6.4:2.95:1.4:0.6:0.05.

[0069] La2O3 was pre-calcined at 1000℃ for 6h, and the raw material was ball-milled in a ball mill for 4h, using isopropanol as a solvent. Then the isopropanol was dried at 80℃, and the dried mixture was pre-calcined at 950℃ for 10h. The pre-calcined product was again ground in 2-propanol using a ball mill for 4h, and dried at 80℃ to remove the isopropanol. Then, a 10mm diameter mold was used to press it into a 10mm diameter disc under a cold press, and then calcined at 1200℃ for 6h to obtain the LLZTO luminescent electrolyte.

[0070] In the second step, the method of using CLSM technology to detect the internal dendrite distribution of LLZTO-0.05Eu electrolyte is:

[0071] First, assemble a solid-state battery. The positive electrode of the solid-state battery is a lithium iron phosphate positive electrode, the negative electrode is metallic lithium, and the solid-state electrolyte is the fluorescent LLZTO-0.05Eu electrolyte obtained in the first step. The solid-state battery is assembled in the order of negative electrode shell, shrapnel, stainless steel sheet, lithium sheet, fluorescent LLZTO-0.05Eu electrolyte, and positive electrode sheet. At a set current density, the assembled solid-state battery is charged and discharged. After a set number of cycles, the solid-state battery is disassembled and the electrolyte in the solid-state battery is detected by CLSM.

[0072] Example 4

[0073] A method for detecting electrolyte dendrites in a solid-state battery, the method comprising the steps of:

[0074] The first step is to prepare the fluorescent PVDF-HFP-Li electrolyte;

[0075] In the second step, the CLSM technique was used to detect the dendrite distribution inside the PVDF-HFP-Li electrolyte;

[0076] In the first step, the method for preparing the fluorescent PVDF-HFP-Li electrolyte is:

[0077] Raw materials include: LiTFSI, PVDF-HFP, EuF3, DMF

[0078] The mass ratio of LiTFSI, PVDF-HFP, and EuF3 in the raw materials is 7.5:7.5:1, and DMF is used as the solvent, so that the concentration of LiTFSI is in the range of 25-50 mg mL -1 between.

[0079] Weigh 0.75g LiTFSI and 0.75g PVDF-HFP respectively and dissolve them in 20mL DMF, stir them magnetically at 30℃ for 12h, then add 0.1g EuF3, continue stirring for 12h, then apply the obtained solution on a polytetrafluoroethylene (PTFE) plate with a spatula and dry it in a vacuum oven at 50℃ for at least 48h. Finally, store the obtained electrolyte membrane in a glove box filled with argon. When assembling the battery, cut the electrolyte membrane into 8mm diameter discs for use.

[0080] In the second step, the method of using CLSM technology to detect the internal dendrite distribution of PVDF-HFP-Li electrolyte is:

[0081] First, assemble a solid-state battery. The positive electrode of the solid-state battery is a lithium iron phosphate positive electrode, the negative electrode is metallic lithium, and the solid-state electrolyte is the fluorescent PVDF-HFP-Li electrolyte obtained in the first step. The solid-state battery is assembled in the order of negative electrode shell, shrapnel, stainless steel sheet, lithium sheet, fluorescent PVDF-HFP-Li electrolyte, and positive electrode sheet. At a set current density, the assembled solid-state battery is charged and discharged. After a set number of cycles, the solid-state battery is disassembled and the electrolyte in the solid-state battery is detected by CLSM.

[0082] In summary, the above are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for detecting electrolyte dendrites in a solid-state battery, characterized in that The steps of the method include: The first step is to prepare the fluorescent electrolyte; In the second step, CLSM technology was used to detect the dendrite distribution inside the fluorescent electrolyte.

2. A method for detecting electrolyte dendrites in a solid-state battery according to claim 1, characterized in that: In the first step, the fluorescent electrolyte is a fluorescent NASICON sodium electrolyte, a PVDF-HFP sodium electrolyte, a LLZTO lithium electrolyte, or a PVDF-HFP lithium electrolyte.

3. A method for detecting electrolyte dendrites in a solid-state battery according to claim 2, characterized in that: The method for preparing fluorescent NASICON sodium electrolyte is: Raw materials include Na2CO3, ZrO(NO3)2, SiO2, NaH2PO4, Eu2O3; The molar ratio of Na2CO3, ZrO(NO3)2, SiO2 and NaH2PO4 in the raw materials is 1.5:2:2:1, and Eu2O3 accounts for 2%-20% of the total mass of the raw materials. After the raw materials are mixed, they are ground by a ball mill to obtain a mixture, which is then pre-fired at 900-1000°C to obtain pre-fired powder. The pre-fired powder is then granulated and pressed into tablets. The obtained tablets are pyrolyzed in air to remove the PVB binder used in the granulation, and then sintered again at 1150-1250°C to obtain the fluorescent NASICON electrolyte.

4. A method for detecting electrolyte dendrites in a solid-state battery according to claim 2, characterized in that: The preparation method of PVDF-HFP sodium electrolyte is: The raw materials include: NaTFSI, PVDF-HFP, EuF3, dimethylformamide (DMF); The mass ratio of NaTFSI, PVDF-HFP, and EuF3 in the raw materials is 5:7.5:1, and DMF is used as the solvent, so that the concentration of NaTFSI ranges from 16 to 33 mg mL -1 between. NaTFSI and PVDF-HFP were weighed and dissolved in DMF, magnetically stirred at 30 ° C for 12 h, and then EuF3 was added and stirred for 12 h. The resulting solution was then coated on a polytetrafluoroethylene (PTFE) plate with a spatula and dried in a vacuum oven at 50 ° C for at least 48 h. Finally, the obtained electrolyte membrane was stored in a glove box filled with argon and recorded as PVDF-HFP-Na.

5. A method for detecting electrolyte dendrites in a solid-state battery according to claim 2, characterized in that: The preparation method of LLZTO lithium electrolyte is: The raw materials include LiOH·H2O, ZrO2, La2O3, Ta2O5, and Eu2O3; The molar ratio of LiOH·H2O, La2O3, ZrO2, Ta2O5 and Eu2O3 in the LLTTO raw material is: 6.4:2.95:1.4:0.6:0.

05. La2O3 was pre-calcined at 1000℃ for 6h, and the raw material was ball-milled in a ball mill for 4h, using isopropanol as a solvent. Then the isopropanol was dried at 80℃, and the dried mixture was pre-calcined at 950℃ for 10h. The pre-calcined product was again ground in 2-propanol using a ball mill for 4h, and dried at 80℃ to remove the isopropanol. Then it was calcined at 1200℃ for 6h to obtain the LLZTO luminescent electrolyte, which was recorded as LLZTO-0.05Eu.

6. A method for detecting electrolyte dendrites in a solid-state battery according to claim 2, characterized in that: The preparation method of PVDF-HFP lithium electrolyte is: Raw materials include: LiTFSI, PVDF-HFP, EuF3, DMF; The mass ratio of LiTFSI, PVDF-HFP, and EuF3 in the raw materials is 7.5:7.5:1, and DMF is used as the solvent, so that the concentration of LiTFSI is in the range of 25-50 mg mL -1 between. LiTFSI and PVDF-HFP were weighed and dissolved in dimethylformamide, magnetically stirred at 30 ° C for 12 h, and then EuF3 was added and stirred for 12 h. The resulting solution was then coated on a polytetrafluoroethylene (PTFE) plate with a spatula and dried in a vacuum oven at 50 ° C for at least 48 h. Finally, the obtained electrolyte membrane was stored in a glove box filled with argon and recorded as PVDF-HFP-Li.

7. A method for detecting electrolyte dendrites in a solid-state battery according to claim 2, characterized in that: In the second step, the method of using CLSM technology to detect the internal dendrite distribution of NASICON fluorescent solid electrolyte is: First, assemble a solid-state battery. The positive electrode of the solid-state battery is sodium vanadium phosphate positive electrode, the negative electrode is metallic sodium, and the solid-state electrolyte is the fluorescent NASICON electrolyte obtained in the first step. The solid-state battery is assembled in the order of negative electrode shell, shrapnel, stainless steel sheet, sodium sheet, fluorescent electrolyte, and positive electrode sheet. At a set current density, the assembled solid-state battery is charged and discharged. After a set number of cycles, the solid-state battery is disassembled and the electrolyte in the solid-state battery is detected by CLSM.

8. A method for detecting electrolyte dendrites in a solid-state battery according to claim 7, characterized in that: When using CLSM for detection, the laser excitation wavelength of CLSM is 405nm, and the depth analysis of the fluorescent NASICON electrolyte is carried out at a speed of 4-10μm / min, and images are collected layer by layer. The analysis depth is 15-30μm.

9. A method for detecting electrolyte dendrites in a solid-state battery according to claim 7, characterized in that: The assembled solid-state battery is charged and discharged at a current density of 100 mAg -1 , the number of charge and discharge cycles is 1100.